Assessing Naltrexone Prescribing and Barriers to Initiation for Alcohol Use Disorder: A Multidisciplinary, Multisite Survey - Leung, Jonathan G.; Narayanan, Prasanna P.; Markota, Matej; Miller, Nathaniel E.; Philbrick, Kemuel L.; Burton, M. Caroline; Kirchoff, Robert W. (Frontiers in Psychiatry, 2022)
Objective: To survey barriers in prescribing naltrexone for alcohol use disorder. Methods: A 12-question survey related to naltrexone prescribing patterns, perceptions, and knowledge was sent to 770 prescribers in the departments of internal medicine, family medicine, and psychiatry across a health system with sites in Arizona, Florida, and Minnesota. Results: Responses were obtained and included for 146/770 prescribers (19.0% response rate). Most respondents were in the department of internal medicine (n=94, 64.4%), but the departments of psychiatry (n=22, 15.1%) and family medicine (n=30, 20.5%) were also represented. Only 34 (23.3%) respondents indicated they had prescribed naltrexone in the previous 3 months. The most common reasons for not prescribing naltrexone were “unfamiliarity with naltrexone for treatment of alcohol use disorder” and “patients do not have appropriate follow-up or are not in a formal treatment program.” Compared with those representing internal/family medicine, psychiatry respondents were more likely to prescribe naltrexone and answer knowledge questions correctly. Conclusion: In this survey among primarily nonaddiction-trained prescribers, a disparity was shown for prescribing naltrexone and in knowledge barriers between staff in internal/family medicine and psychiatry. There exist opportunities for education and quality improvement that promote the prescribing of naltrexone for alcohol use disorder by nonaddiction specialists.